2021
DOI: 10.1038/s41588-021-00950-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of 53,400 people with irritable bowel syndrome highlights shared genetic pathways with mood and anxiety disorders

Abstract: Irritable bowel syndrome (IBS) results from disordered brain–gut interactions. Identifying susceptibility genes could highlight the underlying pathophysiological mechanisms. We designed a digestive health questionnaire for UK Biobank and combined identified cases with IBS with independent cohorts. We conducted a genome-wide association study with 53,400 cases and 433,201 controls and replicated significant associations in a 23andMe panel (205,252 cases and 1,384,055 controls). Our study identified and confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 61 publications
10
131
0
1
Order By: Relevance
“…All probabilities were computed with the biochemical prior. Traits: BMI, body mass index (Neale et al, 2021); SCZ, schizophrenia (Psychiatric Genomics Consortium, 2021); IBD, inflammatory bowel disease (de Lange et al, 2017); BPD, bipolar disorder (Mullins et al, 2021); DEP, depression (Howard et al, 2019); PD, Parkinson’s disease (Nalls et al, 2019); MIG, migraine (Canela-Xandri et al, 2018); IBS, irritable bowel syndrome (Eijsbouts et al, 2021). For each trait, the leftmost bar indicates the expected value of the number of causal variants (i.e., the total number of independent detectable signals in the GWAS), considering only putative causal variants with a GWAS p-value smaller than 10 −3 .…”
Section: Resultsmentioning
confidence: 99%
“…All probabilities were computed with the biochemical prior. Traits: BMI, body mass index (Neale et al, 2021); SCZ, schizophrenia (Psychiatric Genomics Consortium, 2021); IBD, inflammatory bowel disease (de Lange et al, 2017); BPD, bipolar disorder (Mullins et al, 2021); DEP, depression (Howard et al, 2019); PD, Parkinson’s disease (Nalls et al, 2019); MIG, migraine (Canela-Xandri et al, 2018); IBS, irritable bowel syndrome (Eijsbouts et al, 2021). For each trait, the leftmost bar indicates the expected value of the number of causal variants (i.e., the total number of independent detectable signals in the GWAS), considering only putative causal variants with a GWAS p-value smaller than 10 −3 .…”
Section: Resultsmentioning
confidence: 99%
“…A recently published genome-wide association study including 53,400 people with IBS and 433,201 controls, identified six independent genetic susceptibility loci for IBS at genome-wide significance (P < 5 × 10 − 8) and all six loci were replicated at Bonferroni significance (P < 0.0083) using data from an independent panel from 23andMe (205,252 cases and 1,384,055 controls). This study reported strong genome-wide association between IBS and mood and anxiety disorders rooted to shared pathogenic pathways [ 30 ]. Due to the important role of serotonin in the brain–gut axis, genetics of serotonergic pathways, especially the serotonin transporter (SERT), have gained a great amount of attention in recent years [ 31 ].…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
“…External factors are dominant, but internal factors such as gut microbiome, gastrointestinal immune system and genetic makeup is also likely to be crucial for the development and progression of symptoms. Here we summarized potential external and internal factors and genetic findings linked to underlying pathophysiological mechanisms of IBS [ 6 , 24 , 26 , 30 , 96 ]. HPA, hypothalamic–pituitary–adrenal axis; ADRA, adrenoceptor-α; aINS, anterior insula; CDC42, cell division cycle 42; CDH1, cadherin 1; CGN, cingulin; CLDN, claudin; COMT, catechol-O-methyltransferase; CRHR1, corticotropin-releasing hormone receptor 1; FGFR4, fibroblast growth factor receptor 4; GLUL, glutamate-ammonia ligase; GPBAR1, G protein-coupled bile acid receptor 1; GRID2IP, GRID2-interacting protein; HTR, 5-hydroxytryptamine receptor; IL, interleukin; KLB, Klotho-β; mir, microRNA; NKRF, nuclear factor-κB-repressing factor; SCN5A, sodium voltage-gated channel α-subunit 5; SLC6A4, solute carrier family 6 member 4; TNF, tumour necrosis factor; TNFSF15, TNF superfamily member 15; TRPV1, transient receptor potential cation channel subfamily V member 1;; NCAM1, Neural Cell Adhesion Molecule 1; CADM2, Cell Adhesion Molecule 2; PHF2, PHD Finger Protein 2; DOCK9, Dedicator Of Cytokinesis 9 …”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
“…Genetic elements are believed to be playing a role in the enteric nervous system ( 21 ), and one study using patient questionnaires that included participants not diagnosed with IBS, proposed a link between six genetic susceptibility loci and IBS ( 22 ). Nevertheless, despite the promise of human genetics the causes of FGID do not appear to be primarily genetically linked.…”
Section: The Life Spectrum and Timingmentioning
confidence: 99%